(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The text analyzes the spectacles Ítaca [Ithaca] (2018) and O agora que demora [The now that’s delayed] (2019), created by the director Christiane Jatahy. Recognized for the creation of a performative, hybrid and political theatre, the artist transits between cultural and geographical frontier zones. Based on assemblages and repetitions the artist’s performative practices relate to certain proposals defined by Rebecca Schneider, especially the conception of “archives as act” and embodied modes of memory.